Identifying metastatic renal cell carcinoma in thyroid fine-needle aspirates by molecular testing. Issue 12 (31st October 2022) - Freeman, Tanner; Taneja, Charit; Ohori, N Paul; Wald, Abigail I; Skaugen, John; Yip, Linwah; Kim, Seungwon; Ferris, Robert L; Nikiforova, Marina N; Roy, Somak; Nikiforov, Yuri E
Abstract : Renal cell carcinoma (RCC) is the most common type of cancer found to metastasize to the thyroid gland. These tumors may represent a diagnostic challenge in cytology. However, most RCC tumors carry VHL alterations, which are rare in primary thyroid tumors. The aim of this study was to evaluate the utility of molecular testing in detecting metastatic RCC in thyroid fine-needle aspiration (FNA) samples. From November 2017 until March 2022, thyroid FNA samples with ThyroSeq v3 results showing both VHL alterations and low/absent expression of thyroid cell markers were analyzed. Eighteen samples from 15 patients met the inclusion criteria. On molecular analysis, deleterious VHL mutations were found in nine (50%) nodules, VHL copy number alteration (CNA) in two (11%), and both mutations and CNA in seven (39%). None of the cases showed mutations commonly found in thyroid tumors. The mean age of these patients was 68 (range, 49–89) years with a male to female ratio of 2:1. Eight (53%) patients had multiple thyroid nodules on ultrasound. On cytology, 14 (78%) nodules were diagnosed as Bethesda III, 2 (11%) as Bethesda IV, and 2 (11%) as Bethesda V. At the time of cytology review, the history of RCC, sometimes remote, was available for ten patients. Of the 14 patients with medical history or surgical follow-up available, all had history of RCC or renal mass or revealed metastatic RCC on thyroidectomy. This study demonstrates that molecular testing can reliably identify metastatic RCC in thyroid nodules with indeterminate cytology, which could improve patient management.